Early life factors and being overweight at 4 years of age among children in Malmö, Sweden - Lindström Martin; Mangrio Elisabeth; Rosvall Maria (BMC, 2010)
Abstract Background Rising rates of obesity and overweight is an increasing public health problem all over the world. Recent research has shown the importance of early life factors in the development of child overweight. However, to the best of our knowledge there are no studies investigating the potential synergistic effect of early life factors and presence of parental overweight on the development of child overweight. Methods The study was population-based and cross-sectional. The study population consisted of children who visited the Child Health Care (CHC) centers in Malmö for their 4-year health check during 2003-2008 and whose parents answered a self-administered questionnaire (n = 9009 children). Results The results showed that having overweight/obese parents was strongly associated with the child being overweight or obese. Furthermore, there was an association between unfavorable early life factors (i.e., mother smoking during pregnancy, presence of secondhand tobacco smoke early in life, high birth weight) and the development of child overweight/obesity at four years of age, while breastfeeding seemed to have a protective role. For example, maternal smoking during pregnancy was associated with an odds ratio (OR) of 1.47 (95% CI: 1.22, 1.76) for overweight and 2.31 (95% CI: 1.68, 3.17) for obesity. The results further showed synergistic effects between parental overweight and exposure to unfavourable early life factors in the development of child overweight. Conclusions The present study shows the importance of early life factors in the development of child overweight and obesity, and thus puts focus on the importance of early targeted interventions.